EKONOMI KREATIF BERLANDASKAN NILAI KRISTIANI: MENGELOLA TALENTA UNTUK KEMANDIRIAN DAN PELAYANAN JEMAAT - Matruty, Dinatonia Jovery (COMMUNITY : Jurnal Pengabdian Kepada Masyarakat, 2025)
The creative economy is a strategic sector that relies on ideas, knowledge, and human creativity to generate added value and enhance competitiveness. In the context of the church, developing a creative economy grounded in Christian values offers an innovative approach to empowering congregations, particularly young generations, to achieve economic independence while strengthening their service. This community engagement program was conducted at GPM Wayame Congregation, involving 50 catechism students aged ?16 years. The program adopted a participatory approach through interactive lectures, group discussions, case studies, and Q&A sessions, covering topics such as the concept of the creative economy, classification of business types, strategies for utilizing local potential, and the integration of faith-based values including honesty, hard work, and service to others. Evaluation was carried out through pre-tests, post-tests, and observations of active participation. The results of the activity showed an increase in participants understanding from 62% to 89%, as well as their ability to identify five main categories of local potential: processed bananas, processed sago, smoked fish, fish floss, fish nuggets, fish scale handicrafts, and bamboo musical instruments. Business ideas generated included packaging innovation, digital marketing, and church bazaars. These findings confirm that the combination of contextual learning and Christian values can effectively enhance creativity, entrepreneurial ethics, and participant motivation. Moving forward, program sustainability can be strengthened through technical training, business mentoring, and the utilization of digital marketing strategies, with potential for replication in other congregations by adapting to their respective local contexts. ABSTRAKEkonomi kreatif merupakan salah satu sektor strategis yang mengandalkan ide, pengetahuan, dan kreativitas manusia untuk menciptakan nilai tambah serta mendorong daya saing. Dalam konteks gereja, pengembangan ekonomi kreatif berlandaskan nilai Kristiani menjadi pendekatan inovatif untuk memberdayakan jemaat, khususnya generasi muda, agar mandiri secara ekonomi sekaligus memperkuat pelayanan. Kegiatan pengabdian ini dilaksanakan di Jemaat GPM Wayame dengan melibatkan 50 siswa katekisasi berusia ?16 tahun. Program dirancang menggunakan metode partisipatif melalui ceramah interaktif, diskusi kelompok, studi kasus, dan tanya jawab, dengan materi mencakup konsep ekonomi kreatif, klasifikasi jenis usaha, strategi pemanfaatan potensi lokal, serta integrasi nilai-nilai iman seperti kejujuran, kerja keras, dan pelayanan kepada sesama. Evaluasi dilakukan melalui pre-test, post-test, dan observasi partisipasi aktif. Hasil kegiatan menunjukkan peningkatan pemahaman peserta dari 62% menjadi 89%, serta kemampuan mengidentifikasi lima kategori potensi lokal utama: olahan pisang, olahan sagu, ikan asap, abon ikan, nugget ikan, kerajinan sisik ikan, dan alat musik bambu. Ide usaha yang dihasilkan mencakup inovasi kemasan, pemasaran digital, dan bazar jemaat. Temuan ini mengonfirmasi bahwa kombinasi pembelajaran kontekstual dengan nilai-nilai Kristiani mampu meningkatkan kreativitas, etika wirausaha, dan motivasi peserta. Ke depan, keberlanjutan program dapat diperkuat melalui pelatihan teknis, pendampingan bisnis, dan pemanfaatan strategi pemasaran digital, serta berpotensi direplikasi di jemaat lain dengan adaptasi konteks lokal masing-masing.